Effet du jeûne du Ramadan et de l`exercice maximal sur le temps de réaction simple et de choix chez des sujets entraînés - Bouhlel, H.; Latiri, I.; Zarrrouk, N.; Bigard, X.; Shephard, R.; Tabka, Z.; Bouhlel, E. (Science & Sports, 2014)
Purpose: The purpose was to assess the effect of Ramadan fasting and maximal exercise on reaction times in young trained men. Methods: Ten young Karate players (age: 18.5 ± 0.5 years, Height: 1.76 ± 0.44 m) were tested on three sessions: during a control period (C), at the end of the first week (R-1), and during the fourth week of Ramadan (R-4). On each occasion, they performed a progressive cycle ergometer test to exhaustion. Maximal oxygen intake ( VO2max ) was determined, using breath-by-breath gas analysis (metabolic cart ZAN 600). Heart rates (HR) and ratings of perceived exertion (RPE) were also recorded before, during and after maximal exercise. Plasma glucose and reaction times (simple reaction time: SRT, and choice reaction time: CRT) were determined before and after exercise. Results: Ramadan observance had no effect on CRT at rest and after 2-leg maximal exercise in our athletes. The only effect of Ramadan was observed on SRT (P < 0.05). In addition, The VO2max , and MAP remained unchanged between the three sessions, this was also associated with no changes on reaction times and glycaemia after maximal exercise. Conclusion: Despite the maintenance of glucose and PMA, SRT was altered during the Ramadan observance. This suggests that Ramadan intermittent fasting is especially a change of lifestyle and its effect on the reaction time would be specific to the nature of the cognitive task. In addition, Maximal exercise of 9-11 minutes duration, eliciting VO2max had no effect on SRT and CRT.